Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1007/bf02540768
|View full text |Cite
|
Sign up to set email alerts
|

Predicting cetane numbers of n‐alcohols and methyl esters from their physical properties

Abstract: Cetane numbers (C#} for the homologous series of straight-chain, saturated n-alcohols, C5-C12 and C14, were determined according to ASTM D 613. Measured C# ranged from 18.2-80.8 and increased linearly with carbon number {CN). Regression analyses developed equations that related various physical properties or molecular characteristics of these alcohols to calculated C#. The degree of relationship between measured and calculated C# was expressed as R 2. The decreasing order of the precision with which these prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
5

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 11 publications
2
55
0
5
Order By: Relevance
“…For example, there is a positive correlation between CN and boiling point of a fatty compound (18). Another work, in which regression analyses were conducted, showed that boiling point was the most reliable property for predicting the CN of fatty compounds (19). It was more reliable than heat of combustion, carbon number, and melting point.…”
Section: Resultsmentioning
confidence: 95%
“…For example, there is a positive correlation between CN and boiling point of a fatty compound (18). Another work, in which regression analyses were conducted, showed that boiling point was the most reliable property for predicting the CN of fatty compounds (19). It was more reliable than heat of combustion, carbon number, and melting point.…”
Section: Resultsmentioning
confidence: 95%
“…Viola et al 17 calculated the experimental CN for FAMEs whose maximal chain length was 22 carbon atoms. Because the oil from peanut seeds contains C24:0 as the FAME with the maximal chain length, the experimental C24:0 CN was calculated here also on the basis of the equation proposed by Freedman and Bagby 15 and the CN of each peanut oil was predicted as the sum of the mass fraction of all the detected FAME.…”
Section: Cetane Number Cnmentioning
confidence: 99%
“…The present work is intended to provide a reliable kinetic model for a methyl ester fuel that is much larger than the previous methyl butanoate. Instead of the 4 carbon atoms chain of methyl butanoate, the current work provides a kinetic mechanism for methyl decanoate (cetane number of about 47 [ 6,7]), with a chain of 10 carbon atoms with a methyl ester group attached ( Figure 1). …”
Section: Introductionmentioning
confidence: 99%